Effectiveness of Acceptance and Commitment Therapy on the Marital Satisfaction and Sexual Performance in Couples with Emotional Divorce - Mohammad Hossein Zebhi Zarchi; Fatemeh Jalayer; Tayebeh Gholamzadeh Bafghi; Elnaz Hajiyousefi; Behnaz Hatamikia; Fattaneh Amirmahmoudi (Iranian Journal of Educational Research)
Objective: The purpose of this study was to examine the impact of acceptance and commitment therapy on marital satisfaction and sexual performance in couples experiencing emotional divorce. Methods: The participants in this research consisted of couples seeking medical assistance in Yazd city. A sample of 30 individuals was selected using an accessible sampling method and divided into two groups: an experimental group and a control group. The experimental group underwent eight treatment sessions based on acceptance and commitment therapy. Data were collected using a questionnaire that measured marital satisfaction and sexual performance. Results: Analysis of the data using covariance analysis revealed that therapy based on acceptance and commitment had a significant impact on reducing marital dissatisfaction and enhancing sexual performance in couples experiencing emotional divorce. Conclusion: The findings of this study suggest that third wave treatments, such as acceptance and commitment therapy, can positively influence emotional well-being and relationship dynamics due to their educational and experiential nature.